Responsabilidade tributária de grupos econômicos - Simões , Raul Costi (2019)
The present work has as scope analysis of the legal limits of the Brazilian legislator for the purpose of assigning tax liability to business companies associated with economic groups. The work is separated in two parts, the first part with the study of tax liability in the brazilian system, since creation of a national tax code, from the types of tax liability foressen in the tax code, in sparse laws and a conception and acceptance to Brazilian doctrine. The second part of the work begins with the types of companies exist in the brazilian legal system, identifying the companies in which the partners do not liability for the obligations of society, evolving to the corporate groups and ending with the fusion of the two parts of the work, identifying the points of meetings between them, since the normative forecasts to the liability of companies belonging to economic groups, as well as an application in practice and the understanding of the brazilian courts, especially the Federal Regional Courts and the Superior Courts of our country system.